In Vitro Profiling of Application Ready Human Surrogate Primary Progenitor Stromal Cell Fractions - Dasari, Vasanthi; Bolimera, Paparao; Gorthi, Leela Krishna; Dravida, Subhadra (Archives of Clinical and Biomedical Research, 2022)
Background: Human progenitor, primary cell-based models are emerging as alternatives to animal systems in discovery and development stages of pharma and biopharmaceutical candidates meant for clinical application. In vitro platforms available for such use including for assessments of human neuro related toxicities and virulence have been rarely reported. We characterized biological discard sourced primary progenitor cells configured as microphysiological systems in vitro to establish phenotype and genotype signatures with reference to pluripotency and neuronal lineage. Methods and results: Tissue based method of stromal cell population isolation method, MACS to generate induced pluripotent cell fractions, conditioning medium to coax neuronal morphologies were employed to generate human microphysiological in vitro primary cellular platforms. The stromal cells, sorted cells and coaxed neuronal like cells (CNC) manifest distinct phenotypes and genotypes. The sorted cells show enrichment of pluripotent gene markers compared to heterogeneous stromal precursor cell population while CNCs show characteristic complementation with Nestin, EN, Tra1, Musashi, NFL genes. Conclusion: We report here an in vitro human biological discard derived primary progenitor cell-based system with innate pluripotent genotype inclined towards neuronal lineage upon induction. Our study offers a possibility that human derived microphysiological systems generated in scale owing to the source advantage may bring novel insights into the design and choice of next generation assessment methodologies in testing neurotoxicity, neurovirulence like non-clinical safety parameters surrounding vaccines and drugs for safe delivery in line with FDA’s advice to the global industry.